Intraoperative navigation and surgical margins in locally advanced malignant midface tumors. (October 2021) - Ranz Colio, A.; Almeida, F.; Haddad Riesgo, A.; Bueno-deVicente, A.; de Leyva, P.; Acero Sanz, J.
Abstract : Introduction: The surgical treatment of midface tumors is often highly complex. The three-dimensional anatomy of the midface and advanced maxillary tumors make anatomical orientation difficult, which increases the risk of affected surgical margins. The main objective is to answer the question: Does intraoperative navigation improve oncological results in complex midface resections? Material and Methods: Thirty-two patients with malignant midface advanced tumors were included.16 patients were prospectively selected and surgery was performed with intraoperative navigation (ION). A control group of 16 patients was retrospectively selected and surgery was performed without ION. A systematic margin analysis was performed selecting 6 surgical margins for each surgical piece and 192 surgical margins in total were analyzed. Results: Squamous carcinoma was the most frequent histological type (56.25% in study group and 68.75% in control group). Complex maxillectomies (types IV-V-VI Brown and Shaw) were performed in 9 of 16 patients in study group (56.25%) and in 2 of 16 (12.5%) in control group. There were 11 of 96 margins affected in study group (11.5%) and 16 of 96 affected margins in control group (16.7%). Chi square test was not statistically significative (p 0.299). The most affected surgical margin was the deep margin in both groups, 9 of 16 (56.25%) in control group and 6 of 11 (54.5%) in the study group. Conclusion: The use of intraoperative navigation facilitates the resection of advanced midface malignancies and it seems to improve tumor-free margin status with less intraoperative complications. However, further prospective trials with a larger cohort are required to confirm these preliminary results.